Answer:
g(-3) + f(-3) = -162
(f - g)(2) = -49
Explanation:
f(x) = -4x + 15
g(x) = 7x³
1)
g(-3) + f(-3)
Evaluate g(-3) and f(-3).
g(-3) = 7(-3)³, f(-3) = -4(-3) + 15
7(-3)³ + -4(-3) + 15
Evaluate (-3) to the third power.
7(-27) + -4(-3) + 15
Multiply.
-189 + 12 + 15
Add.
-177 + 15
-162.
2)
(f - g)(2) = f(2) - g(2)
Evaluate f(2) and g(2)
f(2) = -4(2) + 15
f(2) = -8 + 15
f(2) = 7
g(2) = 7(2)³
g(2) = 7(8)
g(2) = 56
Now subtract the result of g(2) from the result of f(2)
(f - g)(2) = 7 - 56
(f - g)(2) = -49.